Infecção hospitalar no sítio cirúrgico: análise dos fatores de risco - Pinheiro, Maicon (2013)
This thesis aims to instigate the veterinary community to reflect on the theme, as well as to provide some concepts and information which may help in the diagnosis and also to fight against infection in hospitals, emphasizing the cats and dogs postsurgical infections. To do this, during six months the extrinsic and intrinsic factors related to the infection in cats and dogs in the surgical site in the Veterinary Hospital from the Federal University of Santa Maria (HVU-UFSM) were evaluated. This evaluation is described in the thesis in two papers. In the first paper the autoclave has been checked through chemical and biological tests accomplished every fortnight in the morning; all the tests presented a negative result for the bacterial growth, showing the process of sterilization is efficient. In the second paper the aim was to evaluate the frequency of infection in the surgical site of 156 animals that have underwent surgery at HVU-UFSM, which were submitted to elective and nonelective surgeries of soft tissues and orthopedic ones, without implants. The rate of infection for the surgical site was 1.3% and it is within the limits observed in literature. This way it is possible to conclude that the principles and the procedures used to control surgical infection in this institution are accomplished in an effective way, something that contributes for the low rates of infection in the surgical site.